Effect of planting depth and charcoal levels on barley (Hordeum vulgare L.) yield and components - Muaid Shaker Ali, Muaid Shaker Ali (University of Thi-Qar Journal of agricultural research, 2024)
An experiment was conducted to study the effect of using different levels of charcoal on barley crop planted at different depths in the fields of the College of Agriculture and Marshlands, University of Thi Qar during the fall season of 2023 in order to determine the possibility of providing quantities of water held by charcoal for the germination and growth of barley crop in Thi Qar, Iraq. The charcoal levels were (0, 0.50 and 0.75) kg/1 kg of soil and the planting depth levels were (0, 5 and 10 cm) so that the experimental units were arranged according to factorial experiments using a complete randomized block design with three replications. The results showed the significant effect of the two study factors and their interaction on the studied traits of barley crop, as the significant effect of charcoal was observed at the level of (0.75) kg/1 kg soil on the trait ((plant height (cm), flag leaf area (cm2), tillers per plant, number of spikes per plant, and weight of 100 grains (g)) at a rate of (53.8 cm, 25.04 cm2, 6.856 tillers per plant, 5.30 spikes per plant, 3.942 g) respectively, while the level (0.50 kg/1 kg soil) recorded the highest rate in the traits ((total grain yield (kg per half square meter), biological yield (kg per half square meter), and harvest index%) at a rate of (1.058 kg, 15.71 kg, and 6.57%) respectively. Also, the planting depth (5 cm) had a significant effect on all studied traits and differed from the rest of the planting depths. The best combination was using charcoal at a level of (0.5 kg per 1 kg of soil) with a depth of (5 cm), which confirms the importance of using charcoal to improve soil properties and provide water for the crop to grow well and give the best yield.